A9.12 Non-Canonical NF-Kappab Signaling Induces a Proangiogenic Response in Rheumatoid Arthritis Synovial Fibroblasts and Endothelial Cells. (25th February 2013) - Maracle, CX; Noort, AR; Zoest, KPM van; Tas, SW
Abstract : Background: Synovial fibroblasts (SF) play a pivotal role in the pathophysiology of rheumatoid arthritis (RA). RASF not only promote inflammation and cartilage destruction of the joint, but also stimulate angiogenesis. Angiogenesis allows for increased leukocyte entry into the inflamed synovium and is regarded as a switch from acute to chronic inflammation. The non-canonical nuclear factor kappaB (NF-kB) pathway, with its main regulator NF-kB inducing kinase (NIK), may play a central role in this process. Objectives: To determine the effect of non-canonical NF-kB signalling on pro-angiogenic gene expression in RASF and on the angiogenic potential of human umbilical vein endothelial cells (HUVEC). Methods: RASF were stimulated with lymphotoxin α1 β2 (LT) or LIGHT to activate non-canonical NF-kB signalling, and/or TNF to selectively activate the canonical NF-kB pathway. To effectively block the non-canonical pathway, a dominant negative NIK expressing adenovirus (Ad.NIKdn) was used. Changes in pro-angiogenic gene expression were measured by RT-PCR. Furthermore, to determine the effect on EC proliferation, RASF and HUVEC were co-cultured in the absence or presence of LT, LIGHT, TNF or VEGF EC were visualised through immunohistochemical staining of CD31, which was then semi-quantitatively scored. Results: Gene expression analysis of RASF revealed an increase in mRNA levels of VCAM-1 and IL-6 after stimulation with LT, LIGHT and TNF. Increased expression of IL-8 and MMP-3 was also observed in cells treated with both TNF and LT or LIGHT. These levels were attenuated in cells transduced with Ad.NIKdn prior to stimulation, indicating that the increased expression levels were at least in part non-canonical NF-kB dependent. CCL2 and bFGF were expressed continuously by RASF regardless of stimulation. In the co-culture, proliferation levels of EC increased under all stimulation conditions, with LIGHT inducing almost a 2-fold increase (p < 0.05), which was comparable to VEGF (p < 0.05). Conclusions: RASF contribute to synovial angiogenesis through the expression of adhesion molecules, cytokines, chemokines, matrix remodelling enzymes and growth factors. We demonstrate that the non-canonical NF-kB pathway plays an important role in this process by regulating pro-angiogenic genes and promoting EC proliferation. Further investigation of this pathway could lead to novel non-canonical NF-kB blocking therapeutics that inhibit angiogenesis in RA, thereby halting disease progression.